Guinea-pig treatment with pertussis toxin suppresses macrophage-dependent bronchoconstriction by fMLP and fails to inhibit the effects of PAF. - Kadiri, C. (1992)
1. Bronchoconstriction and thromboxane B2 (TxB2) release following the intra-tracheal administration of the secretagogue N-formyl-L-methionyl-L-leucyl-L-phenylalanine (fMLP) to lungs from pertussis toxin-treated guinea-pigs in vivo and in vitro were inhibited as compared to saline-treated animals, under conditions where the responses to PAF were modified less effectively. 2. The cell target accounting for bronchoconstriction by fMLP and for inhibition by pertussis toxin is located in the airways and is probably the alveolar macrophage. Indeed (a) fMLP-induced superoxide anions and TxB2 formation by alveolar macrophages were inhibited by pertussis toxin given in vivo; (b) Gi proteins of membranes from alveolar macrophages were ADP-ribosylated in vivo by pertussis toxin and (c) bronchoconstriction and TxB2 release in response to the intra-tracheal administration of fMLP to lungs from pertussis toxin-treated animals were restored when alveolar macrophages from control guinea-pigs were transferred into the airways of pertussis toxin-treated animals before lung isolation. 3. Pertussis toxin administered to guinea-pigs in vivo, reduced the subsequent TxB2 formation and superoxide anion release by alveolar macrophages stimulated with PAF, but failed to inhibit PAF-induced bronchoconstriction. 4. Formation of TxB2 by alveolar macrophages following the intra-tracheal administration of fMLP accounts for bronchoconstriction and requires pertussis toxin-sensitive Gi proteins. PAF operates via a different mechanism, which is independent of Gi-like protein and involves mediators other than TxB2 and superoxide anions.